Representasi Pembagian Kerja Dalam Rumah Tangga Keluarga Petani di Desa Sei Bakut Kabupaten Kapuas - Salamah; Varinia Pura Damaiyanti; Sri Hidayah (Prodi Sosiologi FISIP ULM, 2023)
Social construction in society and stereotypes against women have created a double burden on women farmers. This study aims to represent gender differences in farming families. The research used a qualitative approach, Data collection techniques observation, interviews, and documentation. The research was carried out in Sei Bakut Village, Kapuas Kuala District, Kapuas Regency, Central Kalimantan. The results of the study indicate that there is a social construction in the Sei Bakut village community which is instilled from generation to generation from parents to their children that the men in the family are in charge of earning a living and the women in the family. There is a stereotype that women are weak unlike men, and men work with muscle strength and women work with accuracy and neatness so people think that women only work in the domestic sphere and men work in the public sphere. The dual roles experienced by women in Sei Bakut village are roles in the domestic sphere and in the public sphere. Roles in the domestic sphere are roles that are directly related to managing the household, both taking care of children, managing finances, and doing housework such as cooking, washing and cleaning the house. The role in the public sphere is that women participate in earning a living either working on their own land or taking wages on other people's land. There is a social construction in society with stereotypes in a particular group which creates an unequal division of labor both in the household and in the agricultural sector experienced by women so that women spend more time working than men.